Effect of mesenchymal stem cells on movement and urination of rats with spinal cord injury - Silva, Alexandra Justino da; Villanova Junior, Jose Ademar; Fracaro, Leticia; Kuniyoshi Rebelatto, Carmen Lucia; Barchiki, Fabiane; Bezerra de Moura, Sergio Adriane; Dominguez, Alejandro Correa; Abud, Ana Paula Resseti; Locatelli-Dittrich, Rosangela; Slud Brofman, Paulo Roberto; Quitzan, Juliany Gomes [UNESP] (Univ Estadual Londrina, 2015)
Cell therapy has frequently been reported as a possible treatment for spinal trauma in humans and animals; however, without pharmacologically curative action on damage from the primary lesion. In this study, we evaluated the effect of administering human adipose-derived stem cells (hADSC) in rats after spinal cord injury. The hADSC were used between the third and fifth passages and a proportion of cells were transduced for screening in vivo after transplantation. Spinal cord injury was induced with a Fogarty catheter no. 3 inserted into the epidural space with a cuff located at T8 and filled with 80 mu L saline for 5 min. The control group A (n = 12) received culture medium (50 mu L) and group B (n = 12) received hADSC (1.2 x 10(6)) at 7 and 14 days post-injury, in the tail vein. Emptying of the bladder by massage was performed daily for 3 months. Evaluation of functional motor activity was performed daily until 3 months post-injury using the Basso-Beattie-Bresnahan scale. Subsequently, the animals were euthanized and histological analysis of the urinary bladder and spinal cord was performed. Bioluminescence analysis revealed hADSC at the application site and lungs. There was improvement of urinary bladder function in 83.3% animals in group B and 16.66% animals in group A. The analysis of functional motor activity and histology of the spinal cord and urinary bladder demonstrated no significant difference between groups A and B. The results indicate that transplanted hADSC improved urinary function via a telecrine mechanism, namely action at a distance.

A terapia celular tem sido reportada como possibilidade de tratamento para os traumas medulares, frequentes em pessoas e em animais, e que não apresentam cura farmacológica para danos advindos da lesão primária. Foram avaliados os efeitos da aplicação de células-tronco derivadas do tecido adiposo humano (hADSC) em ratos Wistar após lesão medular. As hADSC foram cultivadas, utilizadas entre a terceira e quinta passagens e parte delas foi transduzida para o rastreamento in vivo após o transplante. A lesão medular foi realizada com cateter de Fogarty nº. 3, introduzido no espaço epidural, com cuff localizado em T8 e preenchido com 80 μL de solução salina, por 5 minutos. Os animais do grupo controle (A, n=12) receberam aplicações de meio de cultura (50 μL) e o grupo B (n=12) recebeu duas aplicações de hADSC (1,2 x 106 ), sete e 14 dias pós-lesão, ambas na veia da cauda. O esvaziamento vesical, por massagem, foi efetuado diariamente, durante três meses. As avaliações motoras foram repetidas, diariamente, até três meses pós-lesão, utilizando a escala Basso-Beattie-Bresneham. Após este período os animais foram submetidos à eutanásia e foram realizadas análises histológicas de bexiga urinária e medula espinhal. As análises de bioluminescência revelaram hADSC no local da aplicação e nos pulmões. Houve melhora da função da bexiga urinária em 83,3% dos animais do grupo B e 16,66% dos animais do grupo A. A análise das avaliações motoras e histológicas das medulas espinhais e bexigas urinárias não demonstrou diferenças significativas entre os grupos A e B. Os resultados indicam que as hADSC transplantadas influenciaram a micção, de forma benéfica, por um mecanismo de ação à distância, telécrino.
Efeitos da aplicação das células-tronco mesenquimais sobre a locomoção e micção de ratos submetidos à lesão medular
Keywords: Spinal cord injury; Paraplegia; Urinary incontinence; Cell therapy; Bioluminescence; Lesão medular; Paraplegia; Incontinência urinária; Terapia celular; Bioluminescência